Evaluating the Effectiveness of MES-Based Palm Oil Surfactant in EOR Using Core Flooding and Spontaneous Imbibition Techniques - Rini Setiati; Muhammad Furqon Haryono Bimantoro; Muh.Taufiq Fathaddin; Fahrurrozi Akbar; Bharoto; Iwan Sumirat; Ranggi Ramadhan (Riviera Publishing, 2026)
The increasing decline in oil production from mature reservoirs has encouraged the development of more effective and environmentally friendly Enhanced Oil Recovery (EOR) technologies. Surfactant flooding is a promising chemical EOR method because it can reduce interfacial tension, modify rock wettability, and mobilize trapped residual oil. This study aimed to evaluate the effectiveness of palm oil-based Methyl Ester Sulfonate (MES) surfactant in improving oil recovery through core flooding and spontaneous imbibition techniques. The experiment used Berea sandstone cores with approximately 21% porosity and 100 mD permeability, light crude oil with a gravity of 39°API, and two surfactant solution conditions: 5,000 ppm salinity with 0.5% MES concentration and 10,000 ppm salinity with 2% MES concentration. The results showed that the low-salinity MES solution provided better performance than the high-salinity condition. In the core flooding test, the 5,000 ppm salinity and 0.5% MES solution achieved the highest recovery factor of 84.74%, whereas the 10,000 ppm salinity and 2% MES solution achieved 62.63%. In the spontaneous imbibition test, the low-salinity condition resulted in 51.94% oil recovery, compared with 45.24% under high-salinity conditions. These findings indicate that lower salinity enhances surfactant stability, improves interfacial tension reduction, and promotes oil mobilization. Therefore, palm oil-based MES surfactant demonstrates strong potential as a sustainable chemical EOR agent for sandstone reservoirs.